Survey of photovoltaic industry and policy in Germany and China - Thilo Grau; Molin Huo; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
As building-integrated photovoltaic (PV) solutions can meet around one-third of electricity demand in Germany and China, both countries are interested in exploring this potential. PV technologies have demonstrated significant price reductions, but large-scale global application of PV requires further technology improvements and cost reductions along the value chain. We analyze policies in Germany and China, including deployment support, investment support for manufacturing plants and R&D support measures, and we survey the industrial actors they can encourage to pursue innovation. While deployment support has been successful, investment support for manufacturing in these nations has not been sufficiently tied to innovation incentives, and R&D support has been comparatively weak. The paper concludes with a discussion of the opportunities for global policy coordination.
Keywords: O31; Q42; Q48; 330; photovoltaics; technology policy; innovation; investment support; Photovoltaikanlage; Sonnenenergiepolitik; Forschungs- und Technologiepolitik; Innovation; Investitionspolitik; Förderung regenerativer Energien; Internationale Zusammenarbeit; Deutschland; China